PROBABILISTIC SAFETY ANALYSIS OF LOSS OF COMPONENT COOLING WATER SYSTEM (LOCW) INITIATING EVENT FOR 300 MWE PWR NUCLEAR POWER PLANTS (NPPS) - Z. Arif, H. M.; Kanwal, S.; Habib, U.; Rehman, K. (The Nucleus, 2020)
The probabilistic safety analysis (PSA) is an important tool in ensuring the design safety of a nuclear power plant in relation to potential initiating events that can be caused by random component failures and human errors etc. It estimates the risk in the form of core damage frequency (CDF) and enables us to identify systems for which design improvements or modifications to operational procedures could reduce the probabilities of severe accidents or mitigate their consequences. LOCW initiating event analysis for 300 MWe PWR NPP was evaluated by using small event tree and large fault tree technique. The objective of this analysis was to compare the results of the LOCW initiating event with similar NPPs PSA results. The core damage frequency of LOCW initiating event comes out to be 1.08E-07/yr with total of eleven sequences out of which 06 sequences are leading to Core Damage (CD) state. The failure probabilities of SAF & SMF systems are comes out to be 8.27E-03 & 7.85E-03 respectively. The comparison of results with similar NPPs PSA results showed that the CDF contribution of LOCW is highly sensitive to the initiating event frequency. Similarly it is also observed that the CDF of LOCW event can be improved significantly by taking the credit of SMF after failure of SAF.